2020
DOI: 10.1016/j.ejca.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

High mortality among hospital-acquired COVID-19 infection in patients with cancer: A multicentre observational cohort study

Abstract: Introduction Studies suggest that patients with cancer are more likely to experience severe outcomes from COVID-19. Therefore, cancer centers have undertaken efforts to care for patients with cancer in COVID-free units. Nevertheless, the frequency and relevance of nosocomial transmission of COVID-19 in patients with cancer remain unknown. The goal of this study was to determine the incidence and impact of hospital-acquired COVID-19 in this population and identify predictive factors for COVID-19 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 14 publications
3
68
3
4
Order By: Relevance
“…This increase in mortality in men is related to a higher number of comorbidities, prevalence of smoking, alcohol consumption, and occupational exposures [35 , 36 , 37] . In the present study, differences in mortality due to COVID-19 between the sexes were not identified, as reported in other studies [9 , 11 , 19] . Sex hormones are believed to be important in the immune response; estrogen is known to act as an immune booster, but androgens need to be further investigated for their interaction with COVID-19 [38 , 39] .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This increase in mortality in men is related to a higher number of comorbidities, prevalence of smoking, alcohol consumption, and occupational exposures [35 , 36 , 37] . In the present study, differences in mortality due to COVID-19 between the sexes were not identified, as reported in other studies [9 , 11 , 19] . Sex hormones are believed to be important in the immune response; estrogen is known to act as an immune booster, but androgens need to be further investigated for their interaction with COVID-19 [38 , 39] .…”
Section: Discussionsupporting
confidence: 75%
“…Other studies have also demonstrated higher mortality from COVID-19 in cancer patients, with reported mortality ranging from 9% to 50% [7 , 9 , 12 , 14 , 15 , 17 , 19 , 22] . The results of the present study fall on the lower end of this spectrum, with a 12.4% mortality.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We read with interest the paper by Elkrief et al that reported high mortality amongst healthcare-associated cases of coronavirus-disease-2019 (COVID-19) infection in oncology inpatients, with almost one-fifth of cases attributed to healthcare-associated transmission. [ 1 ] Indeed, healthcare-associated transmission of SARS-CoV-2 poses a substantial problem in cancer centres; in a study describing the impact of COVID-19 on a large cancer centre during the first wave of the pandemic, the majority of patients tested COVID-19-positive after an emergent or elective hospital attendance. [ 2 ] The ongoing pandemic has provided the impetus for introduction of extensive infection-prevention measures in cancer centres, including segregated isolation wards for symptomatic patients, screening of visitors for fever and respiratory symptoms, and heightened COVID-19 surveillance for healthcare workers (HCWs).…”
Section: Ethics Approvalmentioning
confidence: 99%